Celebratory theatre: a response to neoliberalism in the arts. Issue 3 (3rd July 2019) - Kandil, Yasmine; te Bokkel, Hannah
ABSTRACT: As neoliberalism infiltrates the foundations of education and arts-based practices, the authors of this article propose an applied theatre approach, based on the celebration of people who feel marginalised, to defy the notions of individualistic, self-centred, and out-put oriented goals that impact how students engage with and view the arts in their educational programme.